A Survey on Accessible Context-Aware Systems - Abu Doush, Iyad (2020)
At the present time, 15% of the growing world population is estimated to have disabilities and special needs. Disabilities can seriously limit participation in regular life activities, such as controlling home facilities, using transportation services, joining social events, accessing educational contents, to name but a few. With the advancement in ubiquitous and pervasive computing, context-aware systems (CAS) are gaining much attention and demonstrating a stronger association with applications for people with disability. Modern CAS tend to minimize user interactions with the system and provide seamless services, automated awareness, and ambient intelligence and monitoring. CAS for people with disability can detect the surrounding environment, identify an appropriate user interface, interact, and service the user depending on the situation. Nevertheless, a large number of investigations on CAS for people with disability are presented in the literature, limited systems are practically available in the market. In this paper, we survey the literature to thoroughly analyze, evaluate, and critique state-of-the-art research in accessible CAS. Systems are classified according to the type of disability; besides, many interaction models are examined and strategies for making CAS accessible are identified. The investigation confirms the need for frameworks that enable improving security aspects, better exploiting modern hardware systems, performing reliable verification, and further supporting system customization and adaptation.